Too much information? Males convey parasite levels using more signal modalities than females utilise - Pal, Arka; Joshi, Mihir; Thaker, Maria (Journal of Experimental Biology)
Elaborate sexual signals are thought to have evolved and be maintained to serve as honest indicators of signaller quality. One measure of quality is health, which can be affected by parasite infection. Cnemaspis mysoriensis is a diurnal gecko that is often infested with ectoparasites in the wild, and males of this species express visual (coloured gular patches) and chemical (femoral gland secretions) traits that receivers could assess during social interactions. In this paper, we tested whether ectoparasites affect individual health, and whether signal quality is an indicator of ectoparasite levels. In wild lizards, we found that ectoparasite level was negatively correlated with body condition in both sexes. Moreover, some characteristics of both visual and chemical traits in males were strongly associated with ectoparasite levels. Specifically, males with higher ectoparasite levels had yellow gular patches with lower brightness and chroma, and chemical secretions with a lower proportion of aromatic compounds. We then determined whether ectoparasite levels in males influence female behaviour. Using sequential choice trials, wherein females were provided with either the visual or the chemical signals of wild-caught males that varied in ectoparasite level, we found that only chemical secretions evoked an elevated female response towards less parasitised males. Simultaneous choice trials in which females were exposed to the chemical secretions from males that varied in parasite level further confirmed a preference for males with lower parasites loads. Overall, we find that although health (body condition) or ectoparasite load can be honestly advertised through multiple modalities, the parasite-mediated female response is exclusively driven by chemical signals.
Keywords: Insect Science; Molecular Biology; Animal Science and Zoology; Aquatic Science; Physiology; Ecology; Evolution; Behavior and Systematics

On the origin and structure of haplotype blocks - Shipilina, Daria; Pal, Arka; Stankowski, Sean; Chan, Yingguang Frank; Barton, Nicholas H (Molecular Ecology)
The term “haplotype block” is commonly used in the developing field of haplotype-based inference methods. We argue that the term should be defined based on the structure of the Ancestral Recombination Graph (ARG), which contains complete information on the ancestry of a sample. We use simulated examples to demonstrate key features of the relationship between haplotype blocks and ancestral structure, emphasizing the stochasticity of the processes that generate them. Even the simplest cases of neutrality or of a “hard” selective sweep produce a rich structure, often missed by commonly used statistics. We highlight a number of novel methods for inferring haplotype structure, based on the full ARG, or on a sequence of trees, and illustrate how they can be used to define haplotype blocks using an empirical data set. While the advent of new, computationally efficient methods makes it possible to apply these concepts broadly, they (and additional new methods) could benefit from adding features to explore haplotype blocks, as we define them. Understanding and applying the concept of the haplotype block will be essential to fully exploit long and linked-read sequencing technologies.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

Slower-X: Reduced efficiency of selection in the early stages of X chromosome evolution - Mrnjavac, Andrea; Khudiakova, Kseniia; Barton, Nicholas H; Vicoso, Beatriz (Evolution Letters)
Differentiated X chromosomes are expected to have higher rates of adaptive divergence than autosomes, if new beneficial mutations are recessive (the “faster-X effect”), largely because these mutations are immediately exposed to selection in males. The evolution of X chromosomes after they stop recombining in males, but before they become hemizygous, has not been well explored theoretically. We use the diffusion approximation to infer substitution rates of beneficial and deleterious mutations under such a scenario. Our results show that selection is less efficient on diploid X loci than on autosomal and hemizygous X loci under a wide range of parameters. This “slower-X” effect is stronger for genes affecting primarily (or only) male fitness, and for sexually antagonistic genes. These unusual dynamics suggest that some of the peculiar features of X chromosomes, such as the differential accumulation of genes with sex-specific functions, may start arising earlier than previously appreciated.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

Role of natural transformation in the evolution of small cryptic plasmids in Synechocystis sp. PCC 6803 - Nies, Fabian; Wein, Tanita; Hanke, Dustin M.; Springstein, Benjamin L; Alcorta, Jaime; Taubenheim, Claudia; Dagan, Tal (Environmental Microbiology Reports)
Small cryptic plasmids have no clear effect on the host fitness and their functional repertoire remains obscure. The naturally competent cyanobacterium Synechocystis sp. PCC 6803 harbours several small cryptic plasmids; whether their evolution with this species is supported by horizontal transfer remains understudied. Here, we show that the small cryptic plasmid DNA is transferred in the population exclusively by natural transformation, where the transfer frequency of plasmid‐encoded genes is similar to that of chromosome‐encoded genes. Establishing a system to follow gene transfer, we compared the transfer frequency of genes encoded in cryptic plasmids pCA2.4 (2378 bp) and pCB2.4 (2345 bp) within and between populations of two Synechocystis sp. PCC 6803 labtypes (termed Kiel and Sevilla). Our results reveal that plasmid gene transfer frequency depends on the recipient labtype. Furthermore, gene transfer via whole plasmid uptake in the Sevilla labtype ranged among the lowest detected transfer rates in our experiments. Our study indicates that horizontal DNA transfer via natural transformation is frequent in the evolution of small cryptic plasmids that reside in naturally competent organisms. Furthermore, we suggest that the contribution of natural transformation to cryptic plasmid persistence in Synechocystis is limited.
Keywords: Agricultural and Biological Sciences (miscellaneous); Ecology; Evolution; Behavior and Systematics

Integrating top‐down and bottom‐up approaches to understand the genetic architecture of speciation across a monkeyflower hybrid zone - Stankowski, Sean; Chase, Madeline A.; McIntosh, Hanna; Streisfeld, Matthew A. (Molecular Ecology)
Understanding the phenotypic and genetic architecture of reproductive isolation is a long‐standing goal of speciation research. In several systems, large‐effect loci contributing to barrier phenotypes have been characterized, but such causal connections are rarely known for more complex genetic architectures. In this study, we combine “top‐down” and “bottom‐up” approaches with demographic modelling toward an integrated understanding of speciation across a monkeyflower hybrid zone. Previous work suggests that pollinator visitation acts as a primary barrier to gene flow between two divergent red‐ and yellow‐flowered ecotypes of Mimulus aurantiacus . Several candidate isolating traits and anonymous single nucleotide polymorphism loci under divergent selection have been identified, but their genomic positions remain unknown. Here, we report findings from demographic analyses that indicate this hybrid zone formed by secondary contact, but that subsequent gene flow was restricted by widespread barrier loci across the genome. Using a novel, geographic cline‐based genome scan, we demonstrate that candidate barrier loci are broadly distributed across the genome, rather than mapping to one or a few “islands of speciation.” Quantitative trait locus (QTL) mapping reveals that most floral traits are highly polygenic, with little evidence that QTL colocalize, indicating that most traits are genetically independent. Finally, we find little evidence that QTL and candidate barrier loci overlap, suggesting that some loci contribute to other forms of reproductive isolation. Our findings highlight the challenges of understanding the genetic architecture of reproductive isolation and reveal that barriers to gene flow other than pollinator isolation may play an important role in this system.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

The scorpionfly (Panorpa cognata) genome highlights conserved and derived features of the peculiar dipteran X chromosome - Lasne, Clementine; Elkrewi, Marwan N; Toups, Melissa A; Layana Franco, Lorena Alexandra; Macon, Ariana; Vicoso, Beatriz (Molecular Biology and Evolution)
Many insects carry an ancient X chromosome - the Drosophila Muller element F - that likely predates their origin. Interestingly, the X has undergone turnover in multiple fly species (Diptera) after being conserved for more than 450 MY. The long evolutionary distance between Diptera and other sequenced insect clades makes it difficult to infer what could have contributed to this sudden increase in rate of turnover. Here, we produce the first genome and transcriptome of a long overlooked sister-order to Diptera: Mecoptera. We compare the scorpionfly Panorpa cognata X-chromosome gene content, expression, and structure, to that of several dipteran species as well as more distantly-related insect orders (Orthoptera and Blattodea). We find high conservation of gene content between the mecopteran X and the dipteran Muller F element, as well as several shared biological features, such as the presence of dosage compensation and a low amount of genetic diversity, consistent with a low recombination rate. However, the two homologous X chromosomes differ strikingly in their size and number of genes they carry. Our results therefore support a common ancestry of the mecopteran and ancestral dipteran X chromosomes, and suggest that Muller element F shrank in size and gene content after the split of Diptera and Mecoptera, which may have contributed to its turnover in dipteran insects.
Keywords: Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Professor Kerstin Johannesson–winner of the 2022 Molecular Ecology Prize - Westram, Anja M; Butlin, Roger (Molecular Ecology)
Kerstin Johannesson is a marine ecologist and evolutionary biologist based at the Tjärnö Marine Laboratory of the University of Gothenburg, which is situated in the beautiful Kosterhavet National Park on the Swedish west coast. Her work, using marine periwinkles (especially Littorina saxatilis and L. fabalis) as main model systems, has made a remarkable contribution to marine evolutionary biology and our understanding of local adaptation and its genetic underpinnings.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

Why did the Wolbachia transinfection cross the road? Drift, deterministic dynamics, and disease control - Turelli, Michael; Barton, Nicholas H (Evolution Letters)
Maternally inherited Wolbachia transinfections are being introduced into natural mosquito populations to reduce the transmission of dengue, Zika, and other arboviruses. Wolbachia-induced cytoplasmic incompatibility provides a frequency-dependent reproductive advantage to infected females that can spread transinfections within and among populations. However, because transinfections generally reduce host fitness, they tend to spread within populations only after their frequency exceeds a critical threshold. This produces bistability with stable equilibrium frequencies at both 0 and 1, analogous to the bistability produced by underdominance between alleles or karyotypes and by population dynamics under Allee effects. Here, we analyze how stochastic frequency variation produced by finite population size can facilitate the local spread of variants with bistable dynamics into areas where invasion is unexpected from deterministic models. Our exemplar is the establishment of wMel Wolbachia in the Aedes aegypti population of Pyramid Estates (PE), a small community in far north Queensland, Australia. In 2011, wMel was stably introduced into Gordonvale, separated from PE by barriers to A. aegypti dispersal. After nearly 6 years during which wMel was observed only at low frequencies in PE, corresponding to an apparent equilibrium between immigration and selection, wMel rose to fixation by 2018. Using analytic approximations and statistical analyses, we demonstrate that the observed fixation of wMel at PE is consistent with both stochastic transition past an unstable threshold frequency and deterministic transformation produced by steady immigration at a rate just above the threshold required for deterministic invasion. The indeterminacy results from a delicate balance of parameters needed to produce the delayed transition observed. Our analyses suggest that once Wolbachia transinfections are established locally through systematic introductions, stochastic “threshold crossing” is likely to only minimally enhance spatial spread, providing a local ratchet that slightly—but systematically—aids area-wide transformation of disease-vector populations in heterogeneous landscapes.
Keywords: genetics; ecology; evolution; behavior and systematics

The human RNA polymerase I structure reveals an HMG-like docking domain specific to metazoans - Daiß, Julia L; Pilsl, Michael; Straub, Kristina; Bleckmann, Andrea; Höcherl, Mona; Heiss, Florian B; Abascal-Palacios, Guillermo; Ramsay, Ewan P; Tluckova, Katarina; Mars, Jean-Clement; Fürtges, Torben; Bruckmann, Astrid; et al. (Life Science Alliance)
Transcription of the ribosomal RNA precursor by RNA polymerase (Pol) I is a major determinant of cellular growth, and dysregulation is observed in many cancer types. Here, we present the purification of human Pol I from cells carrying a genomic GFP fusion on the largest subunit allowing the structural and functional analysis of the enzyme across species. In contrast to yeast, human Pol I carries a single-subunit stalk, and in vitro transcription indicates a reduced proofreading activity. Determination of the human Pol I cryo-EM reconstruction in a close-to-native state rationalizes the effects of disease-associated mutations and uncovers an additional domain that is built into the sequence of Pol I subunit RPA1. This “dock II” domain resembles a truncated HMG box incapable of DNA binding which may serve as a downstream transcription factor–binding platform in metazoans. Biochemical analysis, in situ modelling, and ChIP data indicate that Topoisomerase 2a can be recruited to Pol I via the domain and cooperates with the HMG box domain–containing factor UBF. These adaptations of the metazoan Pol I transcription system may allow efficient release of positive DNA supercoils accumulating downstream of the transcription bubble.
Keywords: Health; Toxicology and Mutagenesis; Plant Science; Biochemistry; Genetics and Molecular Biology (miscellaneous); Ecology

Modelling membrane reshaping by staged polymerization of ESCRT-III filaments - Jiang, Xiuyun; Harker-Kirschneck, Lena; Vanhille-Campos, Christian Eduardo; Pfitzner, Anna-Katharina; Lominadze, Elene; Roux, Aurélien; Baum, Buzz; Šarić, Anđela (PLOS Computational Biology)
ESCRT-III filaments are composite cytoskeletal polymers that can constrict and cut cell membranes from the inside of the membrane neck. Membrane-bound ESCRT-III filaments undergo a series of dramatic composition and geometry changes in the presence of an ATP-consuming Vps4 enzyme, which causes stepwise changes in the membrane morphology. We set out to understand the physical mechanisms involved in translating the changes in ESCRT-III polymer composition into membrane deformation. We have built a coarse-grained model in which ESCRT-III polymers of different geometries and mechanical properties are allowed to copolymerise and bind to a deformable membrane. By modelling ATP-driven stepwise depolymerisation of specific polymers, we identify mechanical regimes in which changes in filament composition trigger the associated membrane transition from a flat to a buckled state, and then to a tubule state that eventually undergoes scission to release a small cargo-loaded vesicle. We then characterise how the location and kinetics of polymer loss affects the extent of membrane deformation and the efficiency of membrane neck scission. Our results identify the near-minimal mechanical conditions for the operation of shape-shifting composite polymers that sever membrane necks.
Keywords: Computational Theory and Mathematics; Cellular and Molecular Neuroscience; Genetics; Molecular Biology; Ecology; Modeling and Simulation; Ecology; Evolution; Behavior and Systematics

Digest: On the origin of a possible hybrid species - Stankowski, Sean (Evolution)
Hybrid speciation—the origin of new species resulting from the hybridization of genetically divergent lineages—was once considered rare, but genomic data suggest that it may occur more often than once thought. In this study, Noguerales and Ortego found genomic evidence supporting the hybrid origin of a grasshopper that is able to exploit a broader range of host plants than either of its putative parents.
Keywords: General Agricultural and Biological Sciences; Genetics; Ecology; Evolution; Behavior and Systematics

Genetic architecture of repeated phenotypic divergence in Littorina saxatilis evolution - Koch, Eva L.; Ravinet, Mark; Westram, Anja M; Johannesson, Kerstin; Butlin, Roger K. (Evolution)
Chromosomal inversions have been shown to play a major role in a local adaptation by suppressing recombination between alternative arrangements and maintaining beneficial allele combinations. However, so far, their importance relative to the remaining genome remains largely unknown. Understanding the genetic architecture of adaptation requires better estimates of how loci of different effect sizes contribute to phenotypic variation. Here, we used three Swedish islands where the marine snail Littorina saxatilis has repeatedly evolved into two distinct ecotypes along a habitat transition. We estimated the contribution of inversion polymorphisms to phenotypic divergence while controlling for polygenic effects in the remaining genome using a quantitative genetics framework. We confirmed the importance of inversions but showed that contributions of loci outside inversions are of similar magnitude, with variable proportions dependent on the trait and the population. Some inversions showed consistent effects across all sites, whereas others exhibited site-specific effects, indicating that the genomic basis for replicated phenotypic divergence is only partly shared. The contributions of sexual dimorphism as well as environmental factors to phenotypic variation were significant but minor compared to inversions and polygenic background. Overall, this integrated approach provides insight into the multiple mechanisms contributing to parallel phenotypic divergence.
Keywords: General Agricultural and Biological Sciences; Genetics; Ecology; Evolution; Behavior and Systematics

What is reproductive isolation? - Westram, Anja M; Stankowski, Sean; Surendranadh, Parvathy; Barton, Nicholas H (Journal of Evolutionary Biology)
Reproductive isolation (RI) is a core concept in evolutionary biology. It has been the central focus of speciation research since the modern synthesis and is the basis by which biological species are defined. Despite this, the term is used in seemingly different ways, and attempts to quantify RI have used very different approaches. After showing that the field lacks a clear definition of the term, we attempt to clarify key issues, including what RI is, how it can be quantified in principle, and how it can be measured in practice. Following other definitions with a genetic focus, we propose that RI is a quantitative measure of the effect that genetic differences between populations have on gene flow. Specifically, RI compares the flow of neutral alleles in the presence of these genetic differences to the flow without any such differences. RI is thus greater than zero when genetic differences between populations reduce the flow of neutral alleles between populations. We show how RI can be quantified in a range of scenarios. A key conclusion is that RI depends strongly on circumstances—including the spatial, temporal and genomic context—making it difficult to compare across systems. After reviewing methods for estimating RI from data, we conclude that it is difficult to measure in practice. We discuss our findings in light of the goals of speciation research and encourage the use of methods for estimating RI that integrate organismal and genetic approaches.
Keywords: Ecology; Evolution; Behavior and Systematics

Reproductive isolation, speciation, and the value of disagreement: A reply to the commentaries on ‘What is reproductive isolation?’ - Westram, Anja M; Stankowski, Sean; Surendranadh, Parvathy; Barton, Nicholas H (Journal of Evolutionary Biology)
Keywords: Ecology; Evolution; Behavior and Systematics

Direct reciprocity between individuals that use different strategy spaces - Schmid, Laura; Hilbe, Christian; Chatterjee, Krishnendu; Nowak, Martin (PLOS Computational Biology)
In repeated interactions, players can use strategies that respond to the outcome of previous rounds. Much of the existing literature on direct reciprocity assumes that all competing individuals use the same strategy space. Here, we study both learning and evolutionary dynamics of players that differ in the strategy space they explore. We focus on the infinitely repeated donation game and compare three natural strategy spaces: memory-1 strategies, which consider the last moves of both players, reactive strategies, which respond to the last move of the co-player, and unconditional strategies. These three strategy spaces differ in the memory capacity that is needed. We compute the long term average payoff that is achieved in a pairwise learning process. We find that smaller strategy spaces can dominate larger ones. For weak selection, unconditional players dominate both reactive and memory-1 players. For intermediate selection, reactive players dominate memory-1 players. Only for strong selection and low cost-to-benefit ratio, memory-1 players dominate the others. We observe that the supergame between strategy spaces can be a social dilemma: maximum payoff is achieved if both players explore a larger strategy space, but smaller strategy spaces dominate.
Keywords: Computational Theory and Mathematics; Cellular and Molecular Neuroscience; Genetics; Molecular Biology; Ecology; Modeling and Simulation; Ecology; Evolution; Behavior and Systematics

Pipefish locally adapted to low salinity in the Baltic Sea retain phenotypic plasticity to cope with ancestral salinity levels - Goehlich, Henry; Sartoris, Linda; Wagner, Kim-Sara; Wendling, Carolin C.; Roth, Olivia (Frontiers in Ecology and Evolution)
Genetic adaptation and phenotypic plasticity facilitate the migration into new habitats and enable organisms to cope with a rapidly changing environment. In contrast to genetic adaptation that spans multiple generations as an evolutionary process, phenotypic plasticity allows acclimation within the life-time of an organism. Genetic adaptation and phenotypic plasticity are usually studied in isolation, however, only by including their interactive impact, we can understand acclimation and adaptation in nature. We aimed to explore the contribution of adaptation and plasticity in coping with an abiotic (salinity) and a biotic (Vibrio bacteria) stressor using six different populations of the broad-nosed pipefish Syngnathus typhle that originated from either high [14–17 Practical Salinity Unit (PSU)] or low (7–11 PSU) saline environments along the German coastline of the Baltic Sea. We exposed wild caught animals, to either high (15 PSU) or low (7 PSU) salinity, representing native and novel salinity conditions and allowed animals to mate. After male pregnancy, offspring was split and each half was exposed to one of the two salinities and infected with Vibrio alginolyticus bacteria that were evolved at either of the two salinities in a fully reciprocal design. We investigated life-history traits of fathers and expression of 47 target genes in mothers and offspring. Pregnant males originating from high salinity exposed to low salinity were highly susceptible to opportunistic fungi infections resulting in decreased offspring size and number. In contrast, no signs of fungal infection were identified in fathers originating from low saline conditions suggesting that genetic adaptation has the potential to overcome the challenges encountered at low salinity. Offspring from parents with low saline origin survived better at low salinity suggesting genetic adaptation to low salinity. In addition, gene expression analyses of juveniles indicated patterns of local adaptation, trans-generational plasticity and developmental plasticity. In conclusion, our study suggests that pipefish are locally adapted to the low salinity in their environment, however, they are retaining phenotypic plasticity, which allows them to also cope with ancestral salinity levels and prevailing pathogens.
Keywords: ecology; evolution; behavior and systematics; trans-generational plasticity; genetic adaptation; local adaptation; phenotypic plasticity; Baltic Sea; climate change; salinity; syngnathids

Polygenic local adaptation in metapopulations: A stochastic eco‐evolutionary model - Szep, Eniko; Sachdeva, Himani; Barton, Nicholas H (Evolution)
This paper analyses the conditions for local adaptation in a metapopulation with infinitely many islands under a model of hard selection, where population size depends on local fitness. Each island belongs to one of two distinct ecological niches or habitats. Fitness is influenced by an additive trait which is under habitat‐dependent directional selection. Our analysis is based on the diffusion approximation and accounts for both genetic drift and demographic stochasticity. By neglecting linkage disequilibria, it yields the joint distribution of allele frequencies and population size on each island. We find that under hard selection, the conditions for local adaptation in a rare habitat are more restrictive for more polygenic traits: even moderate migration load per locus at very many loci is sufficient for population sizes to decline. This further reduces the efficacy of selection at individual loci due to increased drift and because smaller populations are more prone to swamping due to migration, causing a positive feedback between increasing maladaptation and declining population sizes. Our analysis also highlights the importance of demographic stochasticity, which exacerbates the decline in numbers of maladapted populations, leading to population collapse in the rare habitat at significantly lower migration than predicted by deterministic arguments.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics; General Agricultural and Biological Sciences

Homage to Felsenstein 1981, or why are there so few/many species? - Butlin, Roger K.; Servedio, Maria R.; Smadja, Carole M.; Bank, Claudia; Barton, Nicholas H; Flaxman, Samuel M.; Giraud, Tatiana; Hopkins, Robin; Larson, Erica L.; Maan, Martine E.; Meier, Joana; Merrill, Richard; et al. (Evolution)
If there are no constraints on the process of speciation, then the number of species might be expected to match the number of available niches and this number might be indefinitely large. One possible constraint is the opportunity for allopatric divergence. In 1981, Felsenstein used a simple and elegant model to ask if there might also be genetic constraints. He showed that progress towards speciation could be described by the build‐up of linkage disequilibrium among divergently selected loci and between these loci and those contributing to other forms of reproductive isolation. Therefore, speciation is opposed by recombination, because it tends to break down linkage disequilibria. Felsenstein then introduced a crucial distinction between “two‐allele” models, which are subject to this effect, and “one‐allele” models, which are free from the recombination constraint. These fundamentally important insights have been the foundation for both empirical and theoretical studies of speciation ever since.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics; General Agricultural and Biological Sciences

Using replicate hybrid zones to understand the genomic basis of adaptive divergence - Westram, Anja M; Faria, Rui; Johannesson, Kerstin; Butlin, Roger (Molecular Ecology)
Combining hybrid zone analysis with genomic data is a promising approach to understanding the genomic basis of adaptive divergence. It allows for the identification of genomic regions underlying barriers to gene flow. It also provides insights into spatial patterns of allele frequency change, informing about the interplay between environmental factors, dispersal and selection. However, when only a single hybrid zone is analysed, it is difficult to separate patterns generated by selection from those resulting from chance. Therefore, it is beneficial to look for repeatable patterns across replicate hybrid zones in the same system. We applied this approach to the marine snail Littorina saxatilis, which contains two ecotypes, adapted to wave-exposed rocks vs. high-predation boulder fields. The existence of numerous hybrid zones between ecotypes offered the opportunity to test for the repeatability of genomic architectures and spatial patterns of divergence. We sampled and phenotyped snails from seven replicate hybrid zones on the Swedish west coast and genotyped them for thousands of single nucleotide polymorphisms. Shell shape and size showed parallel clines across all zones. Many genomic regions showing steep clines and/or high differentiation were shared among hybrid zones, consistent with a common evolutionary history and extensive gene flow between zones, and supporting the importance of these regions for divergence. In particular, we found that several large putative inversions contribute to divergence in all locations. Additionally, we found evidence for consistent displacement of clines from the boulder–rock transition. Our results demonstrate patterns of spatial variation that would not be accessible without continuous spatial sampling, a large genomic data set and replicate hybrid zones.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

The CATP-8/P5A-type ATPase functions in multiple pathways during neuronal patterning - Tang, Leo T. H.; Trivedi, Meera; Freund, Jenna; Salazar, Christopher J.; Rahman, Maisha; Ramirez, Nelson; Lee, Garrett; Wang, Yu; Grant, Barth D.; Bülow, Hannes E. (PLOS Genetics)
The assembly of neuronal circuits involves the migrations of neurons from their place of birth to their final location in the nervous system, as well as the coordinated growth and patterning of axons and dendrites. In screens for genes required for patterning of the nervous system, we identified the catp-8/P5A-ATPase as an important regulator of neural patterning. P5A-ATPases are part of the P-type ATPases, a family of proteins known to serve a conserved function as transporters of ions, lipids and polyamines in unicellular eukaryotes, plants, and humans. While the function of many P-type ATPases is relatively well understood, the function of P5A-ATPases in metazoans remained elusive. We show here, that the Caenorhabditis elegans ortholog catp-8/P5A-ATPase is required for defined aspects of nervous system development. Specifically, the catp-8/P5A-ATPase serves functions in shaping the elaborately sculpted dendritic trees of somatosensory PVD neurons. Moreover, catp-8/P5A-ATPase is required for axonal guidance and repulsion at the midline, as well as embryonic and postembryonic neuronal migrations. Interestingly, not all axons at the midline require catp-8/P5A-ATPase , although the axons run in the same fascicles and navigate the same space. Similarly, not all neuronal migrations require catp-8/P5A-ATPase . A CATP-8/P5A-ATPase reporter is localized to the ER in most, if not all, tissues and catp-8/P5A-ATPase can function both cell-autonomously and non-autonomously to regulate neuronal development. Genetic analyses establish that catp-8/P5A-ATPase can function in multiple pathways, including the Menorin pathway, previously shown to control dendritic patterning in PVD, and Wnt signaling, which functions to control neuronal migrations. Lastly, we show that catp-8/P5A-ATPase is required for localizing select transmembrane proteins necessary for dendrite morphogenesis. Collectively, our studies suggest that catp-8/P5A-ATPase serves diverse, yet specific, roles in different genetic pathways and may be involved in the regulation or localization of transmembrane and secreted proteins to specific subcellular compartments.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Nup93 regulates breast tumor growth by modulating cell proliferation and actin cytoskeleton remodeling - Bersini, Simone; Lytle, Nikki K; Schulte, Roberta; Huang, Ling; Wahl, Geoffrey M; HETZER, Martin W (Life Science Alliance)
Nucleoporin 93 (Nup93) expression inversely correlates with the survival of triple-negative breast cancer patients. However, our knowledge of Nup93 function in breast cancer besides its role as structural component of the nuclear pore complex is not understood. Combination of functional assays and genetic analyses suggested that chromatin interaction of Nup93 partially modulates the expression of genes associated with actin cytoskeleton remodeling and epithelial to mesenchymal transition, resulting in impaired invasion of triple-negative, claudin-low breast cancer cells. Nup93 depletion induced stress fiber formation associated with reduced cell migration/proliferation and impaired expression of mesenchymal-like genes. Silencing LIMCH1, a gene responsible for actin cytoskeleton remodeling and up-regulated upon Nup93 depletion, partially restored the invasive phenotype of cancer cells. Loss of Nup93 led to significant defects in tumor establishment/propagation in vivo, whereas patient samples revealed that high Nup93 and low LIMCH1 expression correlate with late tumor stage. Our approach identified Nup93 as contributor of triple-negative, claudin-low breast cancer cell invasion and paves the way to study the role of nuclear envelope proteins during breast cancer tumorigenesis.
Keywords: Health; Toxicology and Mutagenesis; Plant Science; Biochemistry; Genetics and Molecular Biology (miscellaneous); Ecology

The mitochondrial carrier pathway transports non-canonical substrates with an odd number of transmembrane segments - Rampelt, Heike; Sucec, Iva; Bersch, Beate; Horten, Patrick; Perschil, Inge; Martinou, Jean-Claude; van der Laan, Martin; Wiedemann, Nils; Schanda, Paul; Pfanner, Nikolaus (BMC Biology)
Background: The mitochondrial pyruvate carrier (MPC) plays a central role in energy metabolism by transporting pyruvate across the inner mitochondrial membrane. Its heterodimeric composition and homology to SWEET and semiSWEET transporters set the MPC apart from the canonical mitochondrial carrier family (named MCF or SLC25). The import of the canonical carriers is mediated by the carrier translocase of the inner membrane (TIM22) pathway and is dependent on their structure, which features an even number of transmembrane segments and both termini in the intermembrane space. The import pathway of MPC proteins has not been elucidated. The odd number of transmembrane segments and positioning of the N-terminus in the matrix argues against an import via the TIM22 carrier pathway but favors an import via the flexible presequence pathway. Results: Here, we systematically analyzed the import pathways of Mpc2 and Mpc3 and report that, contrary to an expected import via the flexible presequence pathway, yeast MPC proteins with an odd number of transmembrane segments and matrix-exposed N-terminus are imported by the carrier pathway, using the receptor Tom70, small TIM chaperones, and the TIM22 complex. The TIM9·10 complex chaperones MPC proteins through the mitochondrial intermembrane space using conserved hydrophobic motifs that are also required for the interaction with canonical carrier proteins. Conclusions: The carrier pathway can import paired and non-paired transmembrane helices and translocate N-termini to either side of the mitochondrial inner membrane, revealing an unexpected versatility of the mitochondrial import pathway for non-cleavable inner membrane proteins.
Keywords: Biotechnology; Plant Science; General Biochemistry; Genetics and Molecular Biology; Developmental Biology; Cell Biology; Physiology; Ecology; Evolution; Behavior and Systematics; Structural Biology; General Agricultural and Biological Sciences

AXR1 affects DNA methylation independently of its role in regulating meiotic crossover localization - Christophorou, Nicolas; She, Wenjing; Long, Jincheng; Hurel, Aurélie; Beaubiat, Sébastien; Idir, Yassir; Tagliaro-Jahns, Marina; Chambon, Aurélie; Solier, Victor; Vezon, Daniel; Grelon, Mathilde; Feng, Xiaoqi; et al. (PLOS Genetics)
Meiotic crossovers (COs) are important for reshuffling genetic information between homologous chromosomes and they are essential for their correct segregation. COs are unevenly distributed along chromosomes and the underlying mechanisms controlling CO localization are not well understood. We previously showed that meiotic COs are mis-localized in the absence of AXR1, an enzyme involved in the neddylation/rubylation protein modification pathway in Arabidopsis thaliana. Here, we report that in axr1-/-, male meiocytes show a strong defect in chromosome pairing whereas the formation of the telomere bouquet is not affected. COs are also redistributed towards subtelomeric chromosomal ends where they frequently form clusters, in contrast to large central regions depleted in recombination. The CO suppressed regions correlate with DNA hypermethylation of transposable elements (TEs) in the CHH context in axr1-/- meiocytes. Through examining somatic methylomes, we found axr1-/- affects DNA methylation in a plant, causing hypermethylation in all sequence contexts (CG, CHG and CHH) in TEs. Impairment of the main pathways involved in DNA methylation is epistatic over axr1-/- for DNA methylation in somatic cells but does not restore regular chromosome segregation during meiosis. Collectively, our findings reveal that the neddylation pathway not only regulates hormonal perception and CO distribution but is also, directly or indirectly, a major limiting pathway of TE DNA methylation in somatic cells.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

The Moran process on 2-chromatic graphs - Kaveh, Kamran; McAvoy, Alex; Chatterjee, Krishnendu; Nowak, Martin A. (PLOS Computational Biology)
Resources are rarely distributed uniformly within a population. Heterogeneity in the concentration of a drug, the quality of breeding sites, or wealth can all affect evolutionary dynamics. In this study, we represent a collection of properties affecting the fitness at a given location using a color. A green node is rich in resources while a red node is poorer. More colors can represent a broader spectrum of resource qualities. For a population evolving according to the birth-death Moran model, the first question we address is which structures, identified by graph connectivity and graph coloring, are evolutionarily equivalent. We prove that all properly two-colored, undirected, regular graphs are evolutionarily equivalent (where “properly colored” means that no two neighbors have the same color). We then compare the effects of background heterogeneity on properly two-colored graphs to those with alternative schemes in which the colors are permuted. Finally, we discuss dynamic coloring as a model for spatiotemporal resource fluctuations, and we illustrate that random dynamic colorings often diminish the effects of background heterogeneity relative to a proper two-coloring.
Keywords: Ecology; Modelling and Simulation; Computational Theory and Mathematics; Genetics; Ecology; Evolution; Behavior and Systematics; Molecular Biology; Cellular and Molecular Neuroscience

Calcium: The missing link in auxin action - Vanneste, Steffen; Friml, Jiří (Plants)
Due to their sessile lifestyles, plants need to deal with the limitations and stresses imposed by the changing environment. Plants cope with these by a remarkable developmental flexibility, which is embedded in their strategy to survive. Plants can adjust their size, shape and number of organs, bend according to gravity and light, and regenerate tissues that were damaged, utilizing a coordinating, intercellular signal, the plant hormone, auxin. Another versatile signal is the cation, Ca2+, which is a crucial second messenger for many rapid cellular processes during responses to a wide range of endogenous and environmental signals, such as hormones, light, drought stress and others. Auxin is a good candidate for one of these Ca2+-activating signals. However, the role of auxin-induced Ca2+ signaling is poorly understood. Here, we will provide an overview of possible developmental and physiological roles, as well as mechanisms underlying the interconnection of Ca2+ and auxin signaling.
Keywords: Plant Science; Ecology; Ecology; Evolution; Behavior and Systematics

Dynamic association of NUP98 with the human genome - Liang, Yun; Franks, Tobias M.; Marchetto, Maria C.; Gage, Fred H.; HETZER, Martin W (PLoS Genetics)
Faithful execution of developmental gene expression programs occurs at multiple levels and involves many different components such as transcription factors, histone-modification enzymes, and mRNA processing proteins. Recent evidence suggests that nucleoporins, well known components that control nucleo-cytoplasmic trafficking, have wide-ranging functions in developmental gene regulation that potentially extend beyond their role in nuclear transport. Whether the unexpected role of nuclear pore proteins in transcription regulation, which initially has been described in fungi and flies, also applies to human cells is unknown. Here we show at a genome-wide level that the nuclear pore protein NUP98 associates with developmentally regulated genes active during human embryonic stem cell differentiation. Overexpression of a dominant negative fragment of NUP98 levels decreases expression levels of NUP98-bound genes. In addition, we identify two modes of developmental gene regulation by NUP98 that are differentiated by the spatial localization of NUP98 target genes. Genes in the initial stage of developmental induction can associate with NUP98 that is embedded in the nuclear pores at the nuclear periphery. Alternatively, genes that are highly induced can interact with NUP98 in the nuclear interior, away from the nuclear pores. This work demonstrates for the first time that NUP98 dynamically associates with the human genome during differentiation, revealing a role of a nuclear pore protein in regulating developmental gene expression programs.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Including debris cover effects in a distributed model of glacier ablation - Reid, T. D.; Carenzo, M.; Pellicciotti, Francesca; Brock, B. W. (Journal of Geophysical Research: Atmospheres)
Distributed glacier melt models generally assume that the glacier surface consists of bare exposed ice and snow. In reality, many glaciers are wholly or partially covered in layers of debris that tend to suppress ablation rates. In this paper, an existing physically based point model for the ablation of debris-covered ice is incorporated in a distributed melt model and applied to Haut Glacier d'Arolla, Switzerland, which has three large patches of debris cover on its surface. The model is based on a 10 m resolution digital elevation model (DEM) of the area; each glacier pixel in the DEM is defined as either bare or debris-covered ice, and may be covered in snow that must be melted off before ice ablation is assumed to occur. Each debris-covered pixel is assigned a debris thickness value using probability distributions based on over 1000 manual thickness measurements. Locally observed meteorological data are used to run energy balance calculations in every pixel, using an approach suitable for snow, bare ice or debris-covered ice as appropriate. The use of the debris model significantly reduces the total ablation in the debris-covered areas, however the precise reduction is sensitive to the temperature extrapolation used in the model distribution because air near the debris surface tends to be slightly warmer than over bare ice. Overall results suggest that the debris patches, which cover 10% of the glacierized area, reduce total runoff from the glacierized part of the basin by up to 7%.
Keywords: Paleontology; Space and Planetary Science; Earth and Planetary Sciences (miscellaneous); Atmospheric Science; Earth-Surface Processes; Geochemistry and Petrology; Soil Science; Water Science and Technology; Ecology; Aquatic Science; Forestry; Oceanography; Geophysics

Spatial and temporal variability of air temperature on a melting glacier: Atmospheric controls, extrapolation methods and their effect on melt modeling, Juncal Norte Glacier, Chile - Petersen, L.; Pellicciotti, Francesca (Journal of Geophysical Research: Atmospheres)
Temperature data from three Automatic Weather Stations and twelve Temperature Loggers are used to investigate the spatiotemporal variability of temperature over a glacier, its main atmospheric controls, the suitability of extrapolation techniques and their effect on melt modeling. We use data collected on Juncal Norte Glacier, central Chile, during one ablation season. We examine temporal and spatial variability in lapse rates (LRs), together with alternative statistical interpolation methods. The main control over the glacier thermal regime is the development of a katabatic boundary layer (KBL). Katabatic wind occurs at night and in the morning and is eroded in the afternoon. LRs reveal strong diurnal variability, with steeper LRs during the day when the katabatic wind weakens and shallower LRs during the night and morning. We suggest that temporally variable LRs should be used to account for the observed change. They tend to be steeper than equivalent constant LRs, and therefore result in a reduction in simulated melt compared to use of constant LRs when extrapolating from lower to higher elevations. In addition to the temporal variability, the temperature-elevation relationship varies also in space. Differences are evident between local LRs and including such variability in melt modeling affects melt simulations. Extrapolation methods based on the spatial variability of the observations after removal of the elevation trend, such as Inverse Distance Weighting or Kriging, do not seem necessary for simulations of gridded temperature data over a glacier.
Keywords: Paleontology; Space and Planetary Science; Earth and Planetary Sciences (miscellaneous); Atmospheric Science; Earth-Surface Processes; Geochemistry and Petrology; Soil Science; Water Science and Technology; Ecology; Aquatic Science; Forestry; Oceanography; Geophysics

Spatial and temporal variability of meteorological variables at Haut Glacier d'Arolla (Switzerland) during the ablation season 2001: Measurements and simulations - Strasser, Ulrich; Corripio, Javier; Pellicciotti, Francesca; Burlando, Paolo; Brock, Ben; Funk, Martin (Journal of Geophysical Research: Atmospheres)
[1] During the ablation period 2001 a glaciometeorological experiment was carried out on Haut Glacier d'Arolla, Switzerland. Five meteorological stations were installed on the glacier, and one permanent automatic weather station in the glacier foreland. The altitudes of the stations ranged between 2500 and 3000 m a.s.l., and they were in operation from end of May to beginning of September 2001. The spatial arrangement of the stations and temporal duration of the measurements generated a unique data set enabling the analysis of the spatial and temporal variability of the meteorological variables across an alpine glacier. All measurements were taken at a nominal height of 2 m, and hourly averages were derived for the analysis. The wind regime was dominated by the glacier wind (mean value 2.8 m s−1) but due to erosion by the synoptic gradient wind, occasionally the wind would blow up the valley. A slight decrease in mean 2 m air temperatures with altitude was found, however the 2 m air temperature gradient varied greatly and frequently changed its sign. Mean relative humidity was 71% and exhibited limited spatial variation. Mean incoming shortwave radiation and albedo both generally increased with elevation. The different components of shortwave radiation are quantified with a parameterization scheme. Resulting spatial variations are mainly due to horizon obstruction and reflections from surrounding slopes, i.e., topography. The effect of clouds accounts for a loss of 30% of the extraterrestrial flux. Albedos derived from a Landsat TM image of 30 July show remarkably constant values, in the range 0.49 to 0.50, across snow covered parts of the glacier, while albedo is highly spatially variable below the zone of continuous snow cover. These results are verified with ground measurements and compared with parameterized albedo. Mean longwave radiative fluxes decreased with elevation due to lower air temperatures and the effect of upper hemisphere slopes. It is shown through parameterization that this effect would even be more pronounced without the effect of clouds. Results are discussed with respect to a similar study which has been carried out on Pasterze Glacier (Austria). The presented algorithms for interpolating, parameterizing and simulating variables and parameters in alpine regions are integrated in the software package AMUNDSEN which is freely available to be adapted and further developed by the community.
Keywords: Paleontology; Space and Planetary Science; Earth and Planetary Sciences (miscellaneous); Atmospheric Science; Earth-Surface Processes; Geochemistry and Petrology; Soil Science; Water Science and Technology; Ecology; Aquatic Science; Forestry; Oceanography; Geophysics